A refractory castable, an article thereof, recycled aggregate and a preparation method and application thereof

CN122958152APending Publication Date: 2026-10-23ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133267.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]依据本申请的一个或多个实施例提供的一种耐火浇注料、其制品和再生骨料及其制备方法和应用,解决了传统铝电解槽隔热层材料固废利用率低、退役材料难以循环利用、易产生大修渣等技术问题

Benefits of technology

(1)实现了粉煤灰的高值化利用。通过将粉煤灰作为主要原料制备轻质保温骨料和耐火浇注料基质,同时利用粉煤灰中的漂珠和活性组分(Al2O3和SiO2),在无需额外添加昂贵烧结助剂的条件下,获得满足铝电解槽隔热层使用要求的力学和热学性能材料,为粉煤灰的大宗高值消纳提供了新途径。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958152A_ABST
    Figure CN122958152A_ABST
Patent Text Reader

Abstract

The application discloses a refractory castable, an article thereof, a recycled aggregate and a preparation method and application thereof. The refractory castable comprises the following components in percentage by weight: aggregate 50-65%; alumina micropowder 10-15%; second calcium aluminate cement 8-15%; additive 0.2-1%; and the balance is second fly ash; wherein the aggregate is prepared by sintering raw materials at 1500-1600 DEG C, and the raw materials comprise the following components in parts by weight: first fly ash 85-90 parts, first calcium aluminate cement 5-10 parts, and first pore-forming agent 0.01-5 parts; the aggregate comprises first aggregate with a particle size of 0-1 mm, second aggregate with a particle size of 1-3 mm and third aggregate with a particle size of 3-6 mm; the weight ratio of the first aggregate, the second aggregate and the third aggregate is (28-32):(20-25):(45-50); and the additive is a water reducing agent and / or a dispersant. The refractory castable is particularly suitable for a heat insulation layer material of an aluminum electrolysis cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of refractory materials technology, and in particular to a refractory castable, its products, recycled aggregates, their preparation methods and applications. Background Technology

[0002] The insulation layer of aluminum electrolytic cells widely uses clay insulating bricks, clinker bricks or lightweight refractory castables. However, these materials still have some defects: (1) poor resistance to electrolyte penetration: traditional clay bricks have high impurity content and are prone to react with cryolite electrolyte at high temperatures to generate low-melting substances, resulting in material shrinkage and pulverization; (2) insufficient high-temperature strength: the operating temperature of traditional lightweight castables is generally below 1300℃, which is difficult to meet the structural stability requirements of large prebaked cells; (3) it is difficult to balance heat insulation and impermeability. More importantly, these materials have the following prominent problems in production and use: (1) They consume a large amount of high-grade aluminosilicate raw materials and are highly dependent on non-renewable resources; (2) The utilization rate of industrial solid wastes such as fly ash is low. Although some studies have attempted to use fly ash to prepare lightweight refractory materials, it is difficult to achieve large-scale high-value utilization due to unstable product performance or high cost. A large amount of fly ash is still disposed of by stockpiling, causing serious environmental pressure; (3) Decommissioned materials are difficult to recycle. During the service of aluminum electrolytic cells, the materials will permeate and adsorb a large amount of fluoride, and become hazardous waste (overhaul slag) after decommissioning. At present, these hazardous wastes are mainly disposed of by landfill or stockpiling, which not only occupies land resources, but the leakage of soluble fluoride will also cause soil and groundwater pollution, and at the same time cause a huge waste of aluminosilicate refractory resources, making it difficult to achieve high-value recycling.

[0003] Therefore, developing an aluminum electrolytic cell insulation material that can utilize fly ash at a high value, simultaneously achieve the recycling of decommissioned materials, and reduce the amount of overhaul slag is of great significance for the resource utilization of solid waste and the green development of the aluminum industry. Summary of the Invention

[0004] The refractory castable, its products, and recycled aggregates provided by one or more embodiments of this application, as well as their preparation methods and applications, solve the technical problems of low solid waste utilization rate of traditional aluminum electrolytic cell insulation layer materials, difficulty in recycling decommissioned materials, and easy generation of overhaul slag.

[0005] In a first aspect, this application provides a refractory castable comprising, by weight percentage: 50%~65% aggregate; 10%~15% alumina powder; 8%~15% second calcium aluminate cement; 0.2%~1% admixture; and the balance being second fly ash; wherein the aggregate is prepared by sintering raw materials comprising the following weight parts at 1500℃~1600℃: 85 parts~90 parts first fly ash, 5 parts~10 parts first calcium aluminate cement, and 0.01 parts~5 parts first pore-forming agent; the aggregate comprises first aggregate with a particle size of 0mm~1mm, second aggregate with a particle size of 1mm~3mm, and third aggregate with a particle size of 3mm~6mm, wherein the weight ratio of the first aggregate, the second aggregate, and the third aggregate is (28~32):(20~25):(45~50); and the admixture is a water-reducing agent and / or a dispersant.

[0006] Optionally, the first fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, and 28%~32% cenospheres; and / or, the first pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite; and / or, the first calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement.

[0007] Optionally, the aggregate has a porous structure, the apparent porosity of the aggregate is 30%~35%, the closed porosity of the aggregate is 18%~20%, and the pore volume in the aggregate with a pore size range of 20μm~60μm accounts for more than 60% of the total pore volume.

[0008] Optionally, the aggregate has a bulk density of 1.2 g / cm³ to 1.3 g / cm³, a thermal conductivity of 0.25 W / (m·K) to 0.30 W / (m·K) at 350℃, and a room temperature compressive strength ≥8.0 MPa.

[0009] Optionally, the alumina micro powder is active α-Al2O3 micro powder, and the particle size D50 of the alumina micro powder is ≤5μm; and / or, the second calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement; and / or, the admixture includes sodium hexametaphosphate and / or polycarboxylate superplasticizer; and / or, the second fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, 28%~32% cenospheres, and 20%~70% glass microspheres.

[0010] In a second aspect, this application provides a refractory castable product, obtained by sequentially adding water and stirring, casting and molding, and curing and drying the refractory castable product described in the first aspect. The refractory castable product has a room temperature compressive strength ≥20MPa, a compressive strength of 48 MPa ~58MPa after sintering at 1550℃, a thermal conductivity of 0.55 W / (m·K) ~0.65 W / (m·K) at 350℃, a reheat linear change rate of -0.3% to +0.1% after holding at 1350℃ for 3 hours, and an erosion penetration depth of 3.1 mm ~3.7 mm as tested by the cryolite molten salt static crucible method at 960℃.

[0011] A third aspect of this application provides a method for preparing a refractory castable product as described in the second aspect, comprising the following steps: mixing the first fly ash, the first calcium aluminate cement, and the first pore-forming agent in a weight ratio of (85~90):(5~10):(0~5) to obtain a first dry powder mixture; mixing the first dry powder mixture, water, and a polyvinyl alcohol aqueous solution to obtain a first hydrated molding material; molding and drying the first hydrated molding material to obtain a first green embryo; sintering the first green embryo at 1500℃~1600℃, crushing and sieving to obtain the aggregate; mixing and stirring the aggregate, the alumina micro powder, the second calcium aluminate cement, the admixture, the second fly ash, and water to obtain a mixed slurry; and sequentially casting and curing the mixed slurry to obtain a refractory castable product. A fourth aspect of this application provides the application of the refractory castable as described in the first aspect or the refractory castable product as described in the second aspect as a heat insulation layer material in aluminum electrolytic cells or industrial kilns.

[0012] A fifth aspect of this application provides a method for preparing recycled aggregate for refractory castables, comprising the following steps: placing the refractory castable product described in the second aspect as a heat insulation layer in an aluminum electrolysis cell for more than 48 hours, wherein the heat insulation layer of the aluminum electrolysis cell is in contact with cryolite molten salt; crushing and grinding the refractory castable product in contact with cryolite molten salt for more than 48 hours to obtain a first recycled fine powder; mixing and grinding the first recycled fine powder, limestone, and third fly ash to obtain a second recycled fine powder; and heating the second recycled fine powder at 1000℃~125℃. Sintering at 0℃ yields recycled material; the recycled material is mixed with fourth fly ash, third calcium aluminate cement, and second pore-forming agent in a weight ratio of (80~85):(5~10):(5~8):(0.5~1) to obtain a second dry powder mixture; the second dry powder mixture is mixed with water and polyvinyl alcohol aqueous solution to obtain a second hydrated molding material; the second hydrated molding material is molded and dried to obtain a second green embryo; and the second green embryo is sintered at 1500℃~1600℃, crushed and screened to obtain the recycled aggregate.

[0013] Optionally, the particle size of the first recycled fine powder is 50 mesh to 100 mesh; and / or, the particle size D50 of the second recycled fine powder is <0.5 mm.

[0014] Optionally, the mass fraction of limestone in the second recycled fine powder is 15%~25%, and the mass fraction of the third fly ash in the second recycled fine powder is 10%~20%; and / or, the Al2O3 content in the third fly ash is greater than 40%, the SiO2 content in the third fly ash is greater than 45%, the Fe2O3 content in the third fly ash is less than 1.5%, and the cenosphere content in the third fly ash is 28%~32%; and / or, the Al2O3 content in the fourth fly ash is greater than 40%, the SiO2 content in the fourth fly ash is greater than 45%, the Fe2O3 content in the fourth fly ash is less than 1.5%, and the cenosphere content in the fourth fly ash is 28%~32%; and / or, the third calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement; and / or, the second pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite.

[0015] Compared with the prior art, the technical solution provided in this application has the following beneficial effects: (1) High-value utilization of fly ash has been realized. By using fly ash as the main raw material to prepare lightweight thermal insulation aggregate and refractory castable matrix, and by utilizing the cenospheres and active components (Al2O3 and SiO2) in fly ash, materials with mechanical and thermal properties that meet the requirements of the thermal insulation layer of aluminum electrolytic cells can be obtained without the need to add expensive sintering aids. This provides a new way for the large-scale high-value disposal of fly ash.

[0016] (2) The fly ash-based aggregate of this application is obtained by sintering at 1500℃~1600℃ using a specific ratio of first fly ash, first calcium aluminate cement, and first pore-forming agent as raw materials. After sintering, the calcium aluminate cement decomposes to release CaO, which reacts in situ with Al2O3 in the first fly ash to generate a large number of high-temperature resistant platy crystals of calcium hexaaluminate (CA6). These crystals are interspersed in the aggregate matrix, which greatly improves the refractoriness and erosion resistance of the aggregate. The hollow structure of the cenospheres in the first fly ash and the first pore-forming agent work together to form a porous structure. During the sintering process, the decomposition of the first pore-forming agent is the dominant factor in the formation of the porous structure. After the cenospheres soften partially, they combine with the surrounding matrix to stabilize the porous structure in which the visible and closed pores are evenly distributed. The specific ratio of the first fly ash, first calcium aluminate cement, and first pore-forming agent makes the aggregate have low density, low thermal conductivity, and sufficient particle strength, making it suitable as a lightweight aggregate for castables. The aggregate has a bulk density of 1.2 g / cm³ to 1.3 g / cm³, a thermal conductivity of 0.25 W / (m·K) to 0.30 W / (m·K) at 350℃, and a compressive strength of ≥8.0 MPa at room temperature.

[0017] (3) The room temperature compressive strength of the refractory castable of this application reaches up to 22.5 MPa, which is much higher than that of lightweight insulating bricks (1~6 MPa) and better than that of some dense clay bricks (20~30 MPa). After sintering at 1550℃, the strength still remains at 48 MPa~58 MPa, indicating that the refractory castable can be further densified during high-temperature service and has excellent high-temperature structural stability. The core mechanism by which this material can be used as a refractory castable is that during the room temperature (about 20℃~30℃) curing stage, the hydration of the second calcium aluminate cement mainly produces metastable hydrated calcium aluminate (such as CAH). 10 During curing, the metastable phases (C2AH8, C3AH6, and C2AH8) gradually transform into the more stable hydrated tricalcium aluminate (C3AH6), jointly providing initial setting and early strength for the material. Subsequently, during drying, the metastable phase undergoes a dehydration reaction with C3AH6, accompanied by volume shrinkage and structural rearrangement. Although the disintegration of hydration product crystals leads to increased porosity, simultaneously, the active components (mainly SiO2 and Al2O3) in the second calcium aluminate cement and the second fly ash react more rapidly under heating conditions, generating a silicon-containing hydrogarnet phase (C3AS). x H 6-2xThe continuous interwoven structure formed by the dehydrated residual phase of C3AH6 and the silica-containing hydrogarnet, along with the matrix densification effect brought about by the dehydration process, is the main mineralogical basis for the high room-temperature compressive strength of the material after drying. Furthermore, the micro-aggregate filling effect of the alumina micropowder and the optimized particle size distribution of the active glass microspheres in the second fly ash jointly enhance the density of the matrix, further strengthening the compressive strength of the material, thus achieving a high room-temperature compressive strength (≥20MPa). When the material is used in the high-temperature environment of an aluminum electrolysis cell, the second fly ash, alumina micropowder, and cement hydration products in the matrix will undergo further solid-phase reactions to generate high-temperature phases such as mullite, enabling in-situ densification of the structure at high temperatures. Therefore, the high-temperature strength (after sintering at 1550℃) is significantly improved.

[0018] (3) The refractory castable of this application has outstanding resistance to electrolyte penetration. The refractory castable of this application contains Al2O3+SiO2>85%, and the content of other impurities such as Fe2O3, Na2O, K2O, etc. is effectively controlled, avoiding the formation of low-melting substances with cryolite electrolyte under the high-temperature working conditions of aluminum electrolysis cell. According to the static crucible method of cryolite molten salt at 960℃ (refer to YB / T 5295-2018), the erosion penetration depth of the refractory castable of this application is only 3.1 mm ~ 3.7 mm, which is 60~70% lower than that of traditional clay bricks (8~12 mm), and can effectively play the role of auxiliary anti-seepage layer, extending the overall service life of electrolysis cell.

[0019] (4) The refractory castable of this application has good thermal insulation performance and volume stability. The thermal conductivity of the refractory castable of this application at 350℃ is 0.55~0.65 W / (m·K), which is between that of lightweight insulating bricks (0.23~0.65 W / (m·K)) and dense clay bricks (0.9~1.2 W / (m·K)), demonstrating the technical advantage of obtaining higher strength while maintaining good thermal insulation performance. The high-temperature linear change rate of the refractory castable of this application is only -0.3 to +0.1%, which is much smaller than that of traditional materials (-2 to +1%), ensuring the long-term stability of the masonry structure.

[0020] (5) The technical solution of this application is green and environmentally friendly, and can realize the recycling of materials. This application also provides a recycled aggregate for refractory castables, which can be used as the insulation layer of aluminum electrolytic cells by the refractory castables or refractory castable products of this application. After working for a period of time, after calcium-based defluorination stabilization treatment (adding limestone and third fly ash and then sintering at 1000℃~1250℃, the soluble fluoride removal rate is >95%), it can be completely converted into recycled insulation aggregate, which can be reused to prepare castables, forming a closed loop of "fly ash → insulation aggregate → castable → use → recycling → recycled aggregate". For every ton of refractory castables of this application used, about 0.3 tons of fly ash can be reduced, and retired insulation materials are prevented from becoming overhaul slag (hazardous waste), which significantly reduces the amount of overhaul slag generated by electrolytic cells and the disposal cost. Attached Figure Description

[0021] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and disclosure, and together with the description serve to explain the principles of this application and disclosure.

[0022] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a schematic flowchart illustrating a method for preparing a refractory castable product according to some embodiments of this application; Figure 2 This is a schematic flowchart illustrating a method for preparing recycled aggregate for refractory castables according to some other embodiments of this application. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0025] In this application, except where expressly stated, any matters or issues not mentioned are directly applicable to those known in the art without any modification. Furthermore, any implementation described in this application can be freely combined with one or more other implementations described in this application, and the resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this application, and should not be regarded as new content not disclosed or anticipated in this application, unless those skilled in the art consider the combination to be clearly unreasonable.

[0026] Any method steps, processes, and operations described in this application should not be construed as necessarily requiring them to be performed in a particular order as discussed or shown, unless explicitly specified. It should also be understood that additional or alternative steps may be used unless otherwise stated.

[0027] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0028] Any specific numerical values ​​disclosed herein (including the endpoints of numerical ranges) are not limited to their exact values, but should be understood to also include values ​​close to the exact value, such as all possible values ​​within ±5% of the exact value. Furthermore, with respect to the disclosed numerical ranges, one or more new numerical ranges can be obtained by arbitrarily combining the endpoint values ​​of the range, the endpoint values ​​with specific point values ​​within the range, and the specific point values ​​themselves; these new numerical ranges should also be considered as specifically disclosed herein.

[0029] Unless otherwise stated, the terms used herein have the same meaning as commonly understood by those skilled in the art, and if a term is defined herein and its definition differs from the common understanding in the art, the definition herein shall prevail.

[0030] In this article, "CA6" represents CaO and A represents Al2O3.

[0031] This article "CAH" 10 In the text, C represents CaO, A represents Al2O3, and H represents H2O.

[0032] In this article, "C2AH8" represents CaO, A represents Al2O3, and H represents H2O.

[0033] In this article, "C3AH6" represents CaO, A represents Al2O3, and H represents H2O.

[0034] This article "C3AS" x H 6-2x"" is an abbreviation for the chemical formula of the silica-containing hydrogarnet phase, where C represents CaO, A represents Al₂O₃, S represents SiO₂, H represents H₂O, and 0 represents O. <x≤1。

[0035] In this article, "content" refers to mass content.

[0036] Unless otherwise specified, "room temperature" in this article refers to 20℃~30℃.

[0037] First aspect Some embodiments of this application provide a refractory castable, comprising, by weight percentage: 50%~65% aggregate; 10%~15% alumina powder; 8%~15% second calcium aluminate cement; 0.2%~1% admixture; and the balance being second fly ash. The admixture is a water-reducing agent and / or a dispersant.

[0038] The aggregate is prepared by sintering the following raw materials at 1500℃~1600℃ in parts by weight: 85~90 parts of first fly ash, 5~10 parts of first calcium aluminate cement, and 0.01~5 parts of first pore-forming agent. The aggregate includes a first aggregate with a particle size of 0mm~1mm, a second aggregate with a particle size of 1mm~3mm, and a third aggregate with a particle size of 3mm~6mm. The weight ratio of the first, second, and third aggregates is (28~32):(20~25):(45~50).

[0039] This aggregate is a fly ash-based aggregate, obtained by sintering at 1500℃~1600℃ using a specific ratio of first fly ash, first calcium aluminate cement, and first pore-forming agent as raw materials. After sintering, the first calcium aluminate cement decomposes to release CaO, which reacts in situ with Al2O3 in the first fly ash to generate a large number of high-temperature resistant platy crystals of calcium hexaaluminate (CA6). These crystals are interspersed within the aggregate matrix, significantly improving the aggregate's refractoriness and erosion resistance. The hollow structure of the cenospheres in the first fly ash and the pore-forming agent work synergistically to form a porous structure. During sintering, the decomposition of the first pore-forming agent is the dominant factor in the formation of the porous structure. After partial softening, the cenospheres combine with the surrounding matrix, jointly stabilizing the formed porous structure with a uniform distribution of closed and open pores. The specific ratio of first fly ash, first calcium aluminate cement, and first pore-forming agent gives this aggregate low density, low thermal conductivity, and sufficient particle strength, making it suitable as a lightweight aggregate for castables.

[0040] In some embodiments, the Al2O3 content in the first fly ash is greater than 40%, the SiO2 content in the first fly ash is greater than 45%, the Fe2O3 content in the first fly ash is less than 1.5%, and the cenosphere content in the first fly ash is 28%~32%.

[0041] It should be noted that cenospheres have a well-known meaning in the art, referring to hollow microspheres obtained through physical sorting, which are thin-walled, hollow spherical particles with a refractoriness ≥1610℃. Under sintering conditions at 1550℃, although their structure undergoes partial softening and deformation, they can still function as low-density fillers, synergistically forming a porous skeleton of the aggregate with the gases generated by the decomposition of the pore-forming agent. Utilizing the inherent low density and low thermal conductivity of cenospheres in the first fly ash, and through the synergistic construction of a predominantly closed-cell porous structure with the help of a pore-forming agent during sintering, the thermal conductivity of the material is reduced. For example, the cenosphere content in the first fly ash is 28%, 30%, or 32%. The meaning of cenospheres also applies to the second, third, and fourth fly ashes described below.

[0042] In some embodiments, the first pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite.

[0043] In some embodiments, the first calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement. Both CA-70 and CA-80 calcium aluminate cements are commercially available industrial products. Referring to GB / T 201-2015 "Aluminate Cement" standard, the Al2O3 content in CA-70 calcium aluminate cement is... 70% Al2O3 content in CA-80 calcium aluminate cement 80%.

[0044] In some embodiments, the aggregate has a porous structure with uniformly distributed closed pores and open pores, the open pore rate of the aggregate is 30%~35%, the closed pore rate of the aggregate is 18%~20%, and the pore volume in the aggregate with a pore diameter range of 20μm~60μm accounts for more than 60% of the total pore volume.

[0045] In some embodiments, the bulk density of the aggregate is 1.2 g / cm³ to 1.3 g / cm³. For example, the bulk density of the aggregate is 1.2 g / cm³, 1.22 g / cm³, 1.25 g / cm³, 1.28 g / cm³, or 1.3 g / cm³.

[0046] In some embodiments, the thermal conductivity of the aggregate at 350°C is 0.25 W / (m·K) to 0.30 W / (m·K). For example, the thermal conductivity of the aggregate at 350°C is 0.25 W / (m·K), 0.28 W / (m·K), or 0.3 W / (m·K).

[0047] In some embodiments, the room temperature compressive strength of the aggregate is ≥8.0 MPa. Room temperature compressive strength refers to the compressive strength at 20℃~30℃. For example, the room temperature compressive strength of the aggregate is 8.5 MPa.

[0048] In the refractory castable of this application embodiment, during the curing stage at room temperature (approximately 20°C to 30°C), the second calcium aluminate cement hydration mainly produces metastable hydrated calcium aluminate (such as CAH). 10 During curing, the metastable phases (C2AH8, C3AH6, and C2AH8) gradually transform into the more stable hydrated tricalcium aluminate (C3AH6), jointly providing initial setting and early strength for the material. Subsequently, during drying, the metastable phase undergoes a dehydration reaction with C3AH6, accompanied by volume shrinkage and structural rearrangement. Although the disintegration of hydration product crystals leads to increased porosity, simultaneously, the reaction between calcium aluminate cement and the active components (SiO2 and Al2O3) in fly ash accelerates under heating conditions, generating a silicon-containing hydrogarnet phase (C3AS). x H 6-2x The continuous interwoven structure formed by the dehydrated residual phase of C3AH6 and the silica-containing hydrogarnet, along with the matrix densification effect brought about by the dehydration process, is the main mineralogical basis for the high room-temperature compressive strength of the material after drying. Furthermore, the micro-aggregate filling effect of the alumina powder and the optimized particle size distribution of the glass microspheres in the second fly ash jointly enhance the density of the matrix, further strengthening the compressive strength of the material, thus achieving a high room-temperature compressive strength (≥20MPa). When the material is used in the high-temperature environment of an aluminum electrolysis cell, the fly ash, alumina powder, and cement hydration products in the matrix will undergo further solid-phase reactions to generate high-temperature phases such as mullite, enabling in-situ densification of the structure at high temperatures. Therefore, the high-temperature strength (after sintering at 1550℃) is significantly improved.

[0049] It should be noted that alumina micro powder refers to powdery particles with a particle size of less than 20 μm. In some embodiments, the alumina micro powder is active α-Al2O3 micro powder, and the particle size D50 of the alumina micro powder is ≤5 μm.

[0050] In some embodiments, the second calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement. Both CA-70 and CA-80 calcium aluminate cements are commercially available industrial products. Referring to GB / T 201-2015 "Aluminate Cement" standard, the Al2O3 content in CA-70 calcium aluminate cement is... 70% Al2O3 content in CA-80 calcium aluminate cement 80%.

[0051] In some embodiments, the admixtures include sodium hexametaphosphate and / or polycarboxylate superplasticizers.

[0052] In some embodiments, the second fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, 28% to 32% cenospheres, and 20% to 70% glass microspheres.

[0053] Glass microspheres, as is known in the art, refer to solid glassy particles (sinking beads) remaining in fly ash, unlike cenospheres, which are hollow glassy particles. Glass microspheres, together with alumina powder, contribute to particle size distribution and synergistically improve the density of the matrix.

[0054] In some embodiments, the refractory castable further includes a third pore-forming agent. Optionally, the third pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite.

[0055] Second aspect This application provides a refractory castable product through several embodiments, obtained by sequentially adding water and stirring, casting, and curing / drying the refractory castable product described in any embodiment of the first aspect. The room temperature compressive strength of this refractory castable product is ≥20 MPa. The compressive strength of this refractory castable product after sintering at 1550℃ is 48 MPa ~ 58 MPa. The thermal conductivity of this refractory castable product at 350℃ is 0.55 W / (m·K) ~ 0.65 W / (m·K). The reheat linear change rate of this refractory castable product after holding at 1350℃ for 3 hours is -0.3% to +0.1%. The erosion penetration depth of this refractory castable product, tested using the cryolite molten salt static crucible method at 960℃ (according to YB / T 5295-2018 standard), is 3.1 mm ~ 3.7 mm.

[0056] Without restriction, casting can be performed using ordinary mechanical vibration, self-leveling, or any conventional molding method.

[0057] Third aspect Please see Figure 1 This application provides a method for preparing a refractory castable product according to any embodiment of the second aspect described above, comprising the following steps: S1, mix the first fly ash, the first calcium aluminate cement and the first pore-forming agent in a weight ratio of (85~90):(5~10):(0~5) to obtain the first dry powder mixture; S2, the first dry powder mixture, water and polyvinyl alcohol aqueous solution are mixed to obtain the first hydrated molding material; S3, the first hydrated molding material is molded and dried to obtain the first green body; S4, the first green embryo is sintered at 1500℃~1600℃, crushed and screened to obtain aggregate; S5, mix and stir aggregates, alumina powder, second calcium aluminate cement, admixtures, and second fly ash and water to obtain a mixed slurry; and S6, the mixed slurry is poured and cured in sequence to obtain refractory castable products.

[0058] Polyvinyl alcohol aqueous solution functions as both a binder and a pore-forming agent. After burning, it leaves micropores, which, together with the mesopores generated by the decomposition of the pore-forming agent and the hollow structure of the cenospheres themselves, form a micro-meso-macro pore gradient structure, creating a complementary pore size distribution effect. This not only further reduces thermal conductivity, but more importantly, it buffers the propagation of microcracks caused by the mismatch in thermal expansion coefficients between the cenospheres and the matrix, thus further improving the thermal shock resistance of the aggregate while maintaining its lightweight nature. In some embodiments, the mass concentration of the polyvinyl alcohol aqueous solution is 3% to 8%, preferably 5%.

[0059] In some embodiments, in step S2, the amount of water added is 10% to 15% based on the total mass of the first dry powder mixture, water, and polyvinyl alcohol aqueous solution.

[0060] In some embodiments, in step S2, the amount of polyvinyl alcohol aqueous solution added is 3% to 5% based on the total mass of the first dry powder mixture, water, and polyvinyl alcohol aqueous solution.

[0061] Fourth aspect Some embodiments of this application provide the use of refractory castables as described in any embodiment of the first aspect or refractory castable products as described in any embodiment of the second aspect as heat insulation materials in aluminum electrolytic cells or industrial kilns.

[0062] Fifth aspect Please see Figure 2 This application provides a method for preparing recycled aggregate for refractory castables, comprising the following steps: S11, the refractory castable product described in any embodiment of the second aspect is placed in an aluminum electrolysis cell as a heat insulation layer for more than 48 hours, and the heat insulation layer of the aluminum electrolysis cell is in contact with cryolite molten salt. S22, refractory castable products that have been in contact with cryolite molten salt for more than 48 hours are crushed and ground to obtain the first-use fine powder; S33, mix and grind the first batch of fine powder, limestone and third batch of fly ash to obtain the second batch of fine powder; S44, the second batch of fine powder is sintered at 1000℃~1250℃ to obtain recycled material; S55, the recycled material is mixed with the fourth fly ash, the third calcium aluminate cement and the second pore-forming agent in a weight ratio of (80~85):(5~10):(5~8):(0.5~1) to obtain the second dry powder mixture; S66, the second dry powder mixture, water and polyvinyl alcohol aqueous solution are mixed to obtain the second hydrated molding material; S77, the second hydrated molding material is molded and dried to obtain a second green compact; and S88 involves sintering the second green embryo at 1500℃~1600℃, crushing and screening it to obtain recycled aggregate.

[0063] In some embodiments, the particle size of the first-pass fine powder is 50 to 100 mesh.

[0064] In some implementations, the particle size D50 of the second fine powder is less than 0.5 mm.

[0065] The purpose of mixing the first batch of fine powder, limestone, and third batch of fly ash, and then sintering at 1000℃~1250℃, is to perform a defluorination stabilization treatment, so as to effectively control the large amount of harmful fluoride components that permeate and adsorb into the refractory castable during its service in the aluminum electrolysis cell. In some embodiments, the mass fraction of limestone in the second batch of fine powder is 15%~25%, and the mass fraction of the third batch of fly ash in the second batch of fine powder is 10%~20%.

[0066] In some embodiments, the Al2O3 content in the third fly ash is greater than 40%, the SiO2 content in the third fly ash is greater than 45%, the Fe2O3 content in the third fly ash is less than 1.5%, and the cenosphere content in the third fly ash is 28%~32%.

[0067] In some embodiments, the fourth fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, and 28% to 32% cenospheres.

[0068] In some embodiments, the third calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement.

[0069] In some embodiments, the second pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite.

[0070] In some implementations, the temperature of the cryolite molten salt is above 960°C.

[0071] Example To better understand this application, the following description, in conjunction with embodiments, further illustrates this application. However, the scope of protection claimed in this application is not limited to the scope of the embodiments.

[0072] In the following examples, unless otherwise specified, all experimental instruments, raw materials, and quantities involved are commercially available products or can be prepared by known methods. Experimental methods not specifying particular conditions in the examples were performed under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.

[0073] Unless otherwise specified, the specific parameters used in each step of the material preparation process in each embodiment and comparative example are the same.

[0074] Performance testing methods: All performance indicators involved in this application have been tested in accordance with national and industry standards. Bulk density and apparent porosity were determined using the Archimedes method according to GB / T 2997-2015. Closed porosity was calculated by subtracting apparent porosity from true porosity, where true porosity was calculated based on true density (GB / T 5071-2013 gas displacement method) and bulk density. Room temperature compressive strength and high-temperature firing compressive strength were tested according to GB / T 5072-2008. Thermal conductivity was determined using the hot-wire method at 350℃ according to GB / T 5990-2021. Reheat linear change rate was determined according to GB / T 5988-2007 at 1350℃ for 3 hours. Electrolyte penetration resistance was determined using the static crucible method (YB / T 5295-2018 "Test Method for Resistance to Molten Cryolite Erosion of Refractory Materials") after holding in molten cryolite salt at 960℃ for 6 hours. Pore ​​size distribution was determined using mercury porosimetry. Soluble fluoride content was determined according to HJ 873-2017 (water extraction-ion selective electrode method).

[0075] Raw material information The fly ash used in the following examples and comparative examples is high-alumina fly ash enriched with cenospheres through physical sorting. Its chemical composition is: Al₂O₃ 42.5 wt%, SiO₂ 48.3 wt%, Fe₂O₃ 1.2 wt%; loss on ignition 2.5% wt%; cenosphere content 30%; the cenospheres are thin-walled, hollow spherical particles. These cenospheres are high-temperature cenospheres obtained through physical sorting, with a refractoriness ≥1610℃. Under sintering conditions at 1550℃, although their structure undergoes partial softening and deformation, they can still function as low-density fillers and, in conjunction with the gases generated by the decomposition of the pore-forming agent, form the porous skeleton of the aggregate. The pore-forming agent used is either calcium sulfate or magnesium hydroxide, both of analytical grade. The calcium aluminate cement used in the following examples and comparative examples is CA70 calcium aluminate cement with an Al₂O₃ content of approximately 70%. The alumina micropowder is α-Al₂O₃ with a particle size D50 between 2 μm and 3 μm. The polyvinyl alcohol aqueous solution is prepared as a 5% (w / w) polyvinyl alcohol aqueous solution. The admixture is sodium hexametaphosphate or polycarboxylate superplasticizer.

[0076] Example 1: Fly ash-based aggregate S1. Take 100 parts of the above-mentioned fly ash, 5 parts of calcium sulfate (pore-forming agent), and 10 parts of calcium aluminate cement, and mix them in a ball mill for 30 minutes to make the components evenly dispersed, thus obtaining the first dry powder mixture.

[0077] S2, mix 115 parts of the first dry powder mixture, 15 parts of water and 5 parts of polyvinyl alcohol aqueous solution, and stir to obtain the first hydrated molding material.

[0078] S3, the first hydrated molding material is molded under a pressure of 30MPa and then naturally dried to obtain the first green embryo.

[0079] S4. The first green embryo is placed in a high-temperature furnace and sintered at 1550℃ for 2 hours with a heating rate of 5℃ / min, followed by furnace cooling. After sintering, the material is crushed and screened to obtain fly ash-based aggregate with a particle size of 1mm~3mm.

[0080] Performance tests were conducted according to the aforementioned test methods. The fly ash-based aggregate in this embodiment has a bulk density of 1.28 g / cm³, an apparent porosity of 34.2%, a closed porosity of 18.5%, a room temperature compressive strength of 8.5 MPa, a thermal conductivity of 0.28 W / (m·K) at 350℃, and pores with a diameter of 20 μm to 60 μm account for 70% of the total pore volume.

[0081] Example 2: Refractory castable products (mechanical vibration molding) Take 62 parts of fly ash-based aggregate, 18 parts of fly ash, 10 parts of alumina powder, 9 parts of calcium aluminate cement, and 0.3 parts of sodium hexametaphosphate (as an admixture) obtained in Example 1, and mix them evenly in a mixer. Add 7.5 parts of water and stir to form a fluid slurry. Pour the slurry into a mold and vibrate it on a vibrating table for 2 minutes to compact it. After curing at room temperature for 24 hours, demold it and then dry it at 250°C for 24 hours to obtain the refractory castable product. In this example, the finished product is obtained directly after drying, without the need for high-temperature sintering.

[0082] The product was tested for performance according to the aforementioned testing methods. The product's chemical composition is as follows: total Al₂O₃ + SiO₂ content is 86.2%, and Fe₂O₃ content is 1.2%. Physical properties: bulk density 1.58 g / cm³, apparent porosity 21.5%, closed porosity 22.1%. Mechanical properties: room temperature compressive strength after drying at 250℃ is 22.5 MPa; after resintering at 1550℃ for 3 hours, the compressive strength is 58.0 MPa. Thermal properties: thermal conductivity at 350℃ is 0.65 W / (m·K), falling between lightweight insulating bricks (0.23~0.65 W / (m·K)) and dense clay bricks (0.9~1.2 W / (m·K)), demonstrating the technical advantage of achieving higher strength while maintaining good thermal insulation performance; the re-firing linear change rate after holding at 1350℃ for 3 hours is -0.1%. Corrosion resistance: The electrolyte penetration depth was 3.1 mm as tested by the static crucible method with cryolite molten salt at 960℃.

[0083] Test results show that the room temperature compressive strength of the product in this embodiment is 22.5 MPa, which is much higher than the 1~6 MPa of traditional lightweight insulating bricks; after firing at 1550℃, the strength further increases to 58.0 MPa, indicating that the material can be further densified during high-temperature service. The electrolyte penetration depth is reduced by more than 60% compared with traditional clay bricks (8~12 mm).

[0084] Example 3: Refractory castable products (no vibration required) Take 50 parts of fly ash-based aggregate, 22 parts of fly ash, 10 parts of alumina powder, 12 parts of calcium aluminate cement, and 0.2 parts of polycarboxylate superplasticizer (as an admixture) prepared in Example 1 and mix them evenly in a mixer. Add 8.0 parts of water and stir to form a slurry with good fluidity (flowability ≥150mm). Pour the slurry into a mold, where it will compact due to the self-leveling effect of the slurry without the need for mechanical vibration. Cure at room temperature for 24 hours and dry at 250℃ for 24 hours to obtain refractory castable products.

[0085] The product was tested for performance according to the aforementioned testing methods. The product's chemical composition is: 85.5% total Al₂O₃ + SiO₂ content and 1.3% Fe₂O₃ content. Physical properties: bulk density 1.55 g / cm³, apparent porosity 29.5%, closed porosity 11.2%. Mechanical properties: compressive strength at 250℃ (dried) 20.8 MPa, compressive strength after firing at 1550℃ 54.2 MPa. Thermal properties: thermal conductivity at 350℃ 0.62 W / (m·K), reheat linear shrinkage -0.2%. Electrolyte penetration depth: 3.5 mm.

[0086] This embodiment achieves self-leveling molding by adjusting the formula and adding a water-reducing agent, making construction more convenient. The performance is basically equivalent to that of Example 2, proving the feasibility of the self-leveling process.

[0087] Example 4 Take 55 parts of the thermal insulation granular aggregate prepared in Example 1, 18 parts of high-alumina fly ash, 12 parts of alumina powder, 9 parts of calcium aluminate cement, 3 parts of magnesium hydroxide (pore-forming agent), and 0.3 parts of sodium hexametaphosphate, and mix them evenly in a mixer. Add 7.8 parts of water and stir to form a slurry, pour it into a mold, vibrate to compact it, cure at room temperature for 24 hours, and dry at 250℃ for 24 hours to obtain the refractory castable product.

[0088] The product was tested for performance according to the aforementioned test methods. The chemical composition of the product is: total Al₂O₃ + SiO₂ content is 84.5%, and Fe₂O₃ content is 1.3%. Physical properties: bulk density 1.49 g / cm³, apparent porosity 32.0%, closed porosity 14.5%. Mechanical properties: the test results of a compressive strength of 18.5 MPa after drying at 250℃ and a compressive strength of 48.2 MPa after firing at 1550℃ further verify the structural stability of the material under high-temperature service conditions. Thermal properties: thermal conductivity at 350℃ is 0.55 W / (m·K), reheat linear change rate is -0.3%. Electrolyte penetration depth is 3.7 mm. Pore size distribution is 8~35 μm, with an average pore size of 24 μm (measured by mercury porosimetry).

[0089] In this embodiment, magnesium hydroxide is used as a pore-forming agent. Compared with Example 2, the bulk density is further reduced, the closed porosity is increased to 14.5%, the thermal conductivity is reduced to 0.55 W / (m·K), and the thermal insulation performance is better. The strength is slightly reduced, but it is still much higher than that of traditional lightweight thermal insulation bricks.

[0090] Example 5 Recycled Aggregate S11, the refractory castable prepared in Example 2 is decommissioned in a simulated aluminum electrolysis cell environment (960℃ cryolite molten salt erosion for 48h), crushed and ground to a particle size of <100 mesh, and decommissioned waste powder is obtained, which is the first reuse fine powder.

[0091] S22, take 100 parts of the first-use fine powder, 20 parts of limestone, and 15 parts of fly ash, mix them, and grind them until the particle size D50 < 0.5 mm to obtain the second-use fine powder.

[0092] S33, the second batch of fine powder is sintered at 1150℃ for 45 minutes to obtain recycled material.

[0093] Defluorination efficiency testing: The soluble fluoride content in the decommissioned waste (first-use fine powder) before treatment was 2.12%, while the soluble fluoride content in the recovered material decreased to 0.08%, with a soluble fluoride removal rate of 96.2%. The total fluoride content in the recovered material was 0.85% (alkali fusion method), and the leaching toxicity fluoride concentration decreased to 3.2 mg / L (HJ / T 299-2007), which is lower than the hazardous waste limit (100 mg / L), indicating good environmental safety. XRD analysis showed that the main fluoride-containing phase in the recovered material was calcium fluoride (CaF2), with no byproducts such as fluorinated apatite.

[0094] S44. 100 parts of recycled material, 1 part of calcium sulfate, 10 parts of fly ash, and 8 parts of calcium aluminate cement are ball-milled and mixed evenly to obtain the second dry powder mixture.

[0095] S55, 119 parts of the second dry powder mixture, 14 parts of water, and 4 parts of polyvinyl alcohol aqueous solution are molded to obtain the second green body.

[0096] S66, the second green body is sintered at 1550℃ for 2 hours, crushed and screened to obtain recycled aggregate.

[0097] Performance tests were conducted according to the aforementioned test methods. The recycled aggregate had a bulk density of 1.27 g / cm³, an apparent porosity of 37.0%, a closed porosity of 16.5%, a room temperature compressive strength of 8.6 MPa, and a thermal conductivity of 0.30 W / (m·K) at 350℃. Its key performance indicators (bulk density, strength, and thermal conductivity) are at the same level as the fly ash-based aggregate prepared in Example 1, and it can meet the requirements for recycling as a lightweight aggregate for refractory castables.

[0098] The above results demonstrate that the harmful components of the decommissioned waste (first-use fine powder) are effectively controlled after defluorination and stabilization treatment. The recycled aggregate prepared from this recovered material meets performance standards, proving that the defluorination and regeneration process described in this application can achieve the resource-based recycling of decommissioned waste, and that the technical approach is feasible.

[0099] Comparative Example 1 The preparation method is basically the same as that in Example 1, except that the fly ash used contains 28% cenospheres.

[0100] Performance tests were conducted according to the aforementioned test methods. The fly ash-based aggregate in this comparative example has a bulk density of 1.31 g / cm³, an apparent porosity of 44.5%, a closed porosity of 7.9%, a room temperature compressive strength of 8.2 MPa, a thermal conductivity of 0.30 W / (m·K) at 350℃, and pores with a diameter range of 20 μm to 60 μm account for 55% of the total pore volume.

[0101] Comparative Example 2 The preparation method is basically the same as that in Example 1, except that the fly ash used contains 32% cenospheres.

[0102] Performance tests were conducted according to the aforementioned test methods. The fly ash-based aggregate in this comparative example has a bulk density of 1.25 g / cm³, an apparent porosity of 46.5%, a closed porosity of 8.0%, a room temperature compressive strength of 8.0 MPa, a thermal conductivity of 0.27 W / (m·K) at 350℃, and pores with a diameter range of 20 μm to 60 μm account for 61% of the total pore volume.

[0103] Comparative Example 3 The preparation method is basically the same as that in Example 1, except that the fly ash used contains 33% cenospheres.

[0104] Performance tests were conducted according to the aforementioned test methods. The fly ash-based aggregate in this comparative example has a bulk density of 1.23 g / cm³, an apparent porosity of 48.0%, a closed porosity of 7.3%, a room temperature compressive strength of 7.0 MPa, a thermal conductivity of 0.25 W / (m·K) at 350℃, and pores with a diameter range of 20 μm to 60 μm account for 58% of the total pore volume.

[0105] Comparative Example 4 The preparation method is basically the same as that in Example 1, except that the fly ash used contains 27% cenospheres.

[0106] Performance tests were conducted according to the aforementioned test methods. The fly ash-based aggregate in this comparative example has a bulk density of 1.33 g / cm³, an apparent porosity of 43.8%, a closed porosity of 7.8%, a room temperature compressive strength of 7.6 MPa, a thermal conductivity of 0.32 W / (m·K) at 350℃, and pores with a diameter of 20 μm to 60 μm account for 50% of the total pore volume.

[0107] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

[0108] Although preferred embodiments have been described in this specification, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this specification.

[0109] Obviously, those skilled in the art can make various modifications and variations to this specification without departing from its spirit and scope. Therefore, if such modifications and variations fall within the scope of the claims and their equivalents, this specification is also intended to include such modifications and variations.

Claims

1. A refractory castable, characterized in that, Its components, by weight percentage, include: Aggregate 50%~65%; Alumina micro powder 10%~15%; Second calcium aluminate cement: 8%~15%; Admixture 0.2%~1%; The remainder is the second type of fly ash; The aggregate is prepared by sintering raw materials comprising the following parts by weight at 1500℃~1600℃: First, 85-90 parts of fly ash. 5 to 10 parts of the first calcium aluminate cement The first pore-forming agent is 0.01 to 5 parts. The aggregate includes a first aggregate with a particle size of 0 mm to 1 mm, a second aggregate with a particle size of 1 mm to 3 mm, and a third aggregate with a particle size of 3 mm to 6 mm. The weight ratio of the first aggregate, the second aggregate, and the third aggregate is (28 to 32): (20 to 25): (45 to 50). The additive is a water-reducing agent and / or a dispersant.

2. The refractory castable according to claim 1, characterized in that, The first fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, and 28%~32% cenospheres; and / or, The first pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite; and / or, The first calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement.

3. The refractory castable according to claim 1, characterized in that, The aggregate has a porous structure, with an apparent porosity of 30% to 35% and a closed porosity of 18% to 20%. The volume of pores with a diameter of 20 μm to 60 μm accounts for more than 60% of the total pore volume.

4. The refractory castable according to claim 1, characterized in that, The aggregate has a bulk density of 1.2 g / cm³ to 1.3 g / cm³, a thermal conductivity of 0.25 W / (m·K) to 0.30 W / (m·K) at 350℃, and a room temperature compressive strength ≥8.0 MPa.

5. The refractory castable according to claim 1, characterized in that, The alumina micro powder is active α-Al₂O₃ micro powder, and the particle size D50 of the alumina micro powder is ≤5 μm; and / or, The second calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement; and / or, The admixtures include sodium hexametaphosphate and / or polycarboxylate superplasticizers; and / or, The second fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, 28% to 32% cenospheres, and 20% to 70% glass microspheres.

6. A refractory castable product, obtained by sequentially adding water and stirring, casting and molding, and curing and drying the refractory castable according to any one of claims 1 to 5, characterized in that, The refractory castable has a room temperature compressive strength ≥20MPa, a compressive strength of 48 MPa ~58MPa after sintering at 1550℃, a thermal conductivity of 0.55 W / (m·K) ~0.65 W / (m·K) at 350℃, a reheat linear change rate of -0.3% to +0.1% after holding at 1350℃ for 3 hours, and an erosion penetration depth of 3.1 mm ~3.7 mm as tested by the cryolite molten salt static crucible method at 960℃.

7. A method for preparing a refractory castable product as described in claim 6, characterized in that, Includes the following steps: The first fly ash, the first calcium aluminate cement and the first pore-forming agent are mixed in a weight ratio of (85~90):(5~10):(0~5) to obtain the first dry powder mixture; The first dry powder mixture, water, and polyvinyl alcohol aqueous solution are mixed to obtain the first hydrated molding material; The first hydrated molding material is molded and dried to obtain the first green embryo; The first green embryo is sintered at 1500℃~1600℃, crushed and screened to obtain the aggregate; The aggregate, the alumina powder, the second calcium aluminate cement, the admixture, the second fly ash, and water are mixed and stirred to obtain a mixed slurry. as well as The mixed slurry is sequentially cast, molded, cured, and dried to obtain refractory castable products.

8. The application of the refractory castable as described in any one of claims 1 to 5 or the refractory castable product as described in claim 6 as a heat insulation layer material in aluminum electrolytic cells or industrial kilns.

9. A method for preparing recycled aggregate for refractory castables, characterized in that, Includes the following steps: The refractory castable product according to claim 6 is placed in an aluminum electrolysis cell as a heat insulation layer for more than 48 hours, wherein the heat insulation layer of the aluminum electrolysis cell is in contact with cryolite molten salt. Refractory castable products that have been in contact with cryolite molten salt for more than 48 hours are crushed and ground to obtain the first-use fine powder. The first batch of fine powder, limestone, and third batch of fly ash are mixed and ground to obtain the second batch of fine powder; The second batch of fine powder was sintered at 1000℃~1250℃ to obtain recycled material; The recycled material is mixed with the fourth fly ash, the third calcium aluminate cement, and the second pore-forming agent in a weight ratio of (80~85):(5~10):(5~8):(0.5~1) to obtain the second dry powder mixture; The second dry powder mixture, water, and polyvinyl alcohol aqueous solution are mixed to obtain the second hydrated molding material; The second hydrated molding material is molded and dried to obtain the second green embryo; as well as The second green embryo is sintered at 1500℃~1600℃, crushed and screened to obtain the recycled aggregate.

10. The preparation method according to claim 9, characterized in that, The particle size of the fine powder used in the first application is 50-100 mesh; and / or, The particle size D50 of the fine powder used in the second application is less than 0.5 mm.

11. The preparation method according to claim 9, characterized in that, The mass fraction of limestone in the second-stage fine powder is 15%~25%, and the mass fraction of fly ash in the second-stage fine powder is 10%~20%; and / or, The third fly ash contains more than 40% Al2O3, more than 45% SiO2, less than 1.5% Fe2O3, and 28%~32% cenospheres; and / or, The fourth type of fly ash contains an Al2O3 content greater than 40%, an SiO2 content greater than 45%, an Fe2O3 content less than 1.5%, and a cenosphere content of 28%–32%; and / or, The third type of calcium aluminate cement is CA-70 calcium aluminate cement and / or CA-80 calcium aluminate cement; and / or... The second pore-forming agent includes one or more of calcium sulfate, magnesium hydroxide, and dolomite.